2009
DOI: 10.1038/aps.2008.30
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the effect of iptakalim on human pulmonary arterial smooth muscle cell proliferation

Abstract: Aim:To investigate the anti-proliferative effect of iptakalim (Ipt), a newly selective K ATP channel opener, in endothelin-1 (ET-1)-induced human pulmonary arterial smooth muscle cells (PASMCs) using proteomic analysis. Methods: Human PASMCs were incubated with ET-1 (10 -8 mol/L) and ET-1 (10 -8 mol/L) plus iptaklim (10 -5 mol/L) for 24 h. Analysis via 2-DE gel electrophoresis and MALDI-TOF-MS was employed to display the different protein profiles of wholecell protein from cultures of control, ET-1 treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The expression of NUP54 is increased, which is an essential protein present in a multiprotein complex that is primarily required for nuclear protein import . The abnormal expression of NUP54 could inhibit the proliferation of human pulmonary arterial smooth muscle cells by opening the K ATP channel . In psoriatic T cells, increased expression of NUP54 may influence the cell proliferation by affecting nuclear protein import.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of NUP54 is increased, which is an essential protein present in a multiprotein complex that is primarily required for nuclear protein import . The abnormal expression of NUP54 could inhibit the proliferation of human pulmonary arterial smooth muscle cells by opening the K ATP channel . In psoriatic T cells, increased expression of NUP54 may influence the cell proliferation by affecting nuclear protein import.…”
Section: Discussionmentioning
confidence: 99%
“…33 The abnormal expression of NUP54 could inhibit the proliferation of human pulmonary arterial smooth muscle cells by opening the K ATP channel. 34 In psoriatic T cells, increased expression of NUP54 may influence the cell proliferation by affecting nuclear protein import. These genes were not different in MZ-CP.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that iptakalim (14,15), inhibited ET-1 synthesis in cultured endothelial cells and suppressed ET-1-induced proliferation of HPASMCs in vitro (17,25). In a proteomic study, it was found that iptakalim significantly inhibited protein expression of RPL22 in HPASMCs (16). Therefore, we presumed that RPL22 may be involved in the proliferation of HPASMCs.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, RPL22 deficiency has been reported to selectively arrest development of T cells at the β-selection checkpoint by inducing their death (13). Our preceding research showed that iptakalim, a selective K ATP channel opener (14,15), suppressed ET-1-induced HPASMC proliferation and significantly inhibited RPL22 expression in HPASMCs (16). It was presumed that RPL22 may be involved in the proliferation of HPASMCs.…”
Section: Introductionmentioning
confidence: 98%
“…had reported that 27 proteins were up- or down-regulated by ET-1 and then differentially affected by the selective K ATP channel opener iptakalim in normal human pulmonary arterial smooth muscle cells, but these authors did not provide a list of the proteins that differed between untreated and ET-1 stimulated cells. 6 As shown in Figure 2, Dupont et al . characterized 50 proteins as intracellular proteins expressed in human arterial smooth muscle cells through gel-based protein analysis.…”
Section: Discussionmentioning
confidence: 89%